Bored to Death: Improvisations on a Theme. Issue 3 (December 2015) - Frendo, Maria
Abstract : Since Petronius and Ovid wrote about the Sybil lamenting the loss of her freedom, which she had traded for eternal life, boredom has not ceased to fascinate and allure. Plato and Aristotle broached the topic philosophically, followed by a whole range of philosophers, writers, painters, and musicians. In this paper, Maria Frendo traces a genealogy of a host of characters in fiction and literary tradition who are afflicted by boredom, from Petronius' Sybil to Beckett's Vladimir and Estragon, from Shakespeare's Antonio to Tennyson's Lotos-Eaters, from Huysmans' Count des Esseintes to Eliot's Prufrock, but not forgetting woman: signally, through Flaubert's Emma Bovary. The essay's development and focus bear on two further considerations: firstly, the relation of boredom with death and desire, whereby the longing for relief from the situation in which one is trapped is accompanied by disinclination to resist and an accommodation to paralysis; and, secondly, patterns of duality and doubling across a good number of the predicaments depicted. Halfway through, the paper formally performs a boredom and irritation of its own in the process of highlighting existential angst and postmodernist neurosis in literature and the post-literary, and shifts its focus onto the poetry of Baudelaire and Mallarmé. This apparent randomness is deliberate: hence the subtitle 'Improvisations on a Theme', suggestive of thematic and structural characteristics to the paper and its argument.